'Five stars arising': a conversation about applied theatre, precarity, and resilience in Singapore. Issue 1 (2nd January 2021) - Lazaroo, Natalie
ABSTRACT: In Singapore, resilience lies at the heart of the nation's efforts at building a strong civic culture. For those experiencing urban poverty, resilience holds little weight against the national rhetoric of self-reliance and meritocracy as keys to success. This paper presents a three-way conversation between the researcher, applied theatre facilitator, and youth participant, centring on the role applied theatre plays in examining the relationship between resilience and precarity within the cultural and political context of Singapore. It draws on Singapore's national ideas of equality, justice, democracy, peace, and progress as touchstones to guide our reflection.